2021
DOI: 10.3389/fphys.2021.715506
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Influences of Gut Microbiota Dysbiosis on Inflammatory Bowel Disease

Abstract: Inflammatory bowel diseases (IBD) are chronic medical disorders characterized by recurrent gastrointestinal inflammation. While the etiology of IBD is still unknown, the pathogenesis of the disease results from perturbations in both gut microbiota and the host immune system. Gut microbiota dysbiosis in IBD is characterized by depleted diversity, reduced abundance of short chain fatty acids (SCFAs) producers and enriched proinflammatory microbes such as adherent/invasive E. coli and H2S producers. This dysbiosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 313 publications
(458 reference statements)
3
61
0
5
Order By: Relevance
“…Finally, it should be mentioned that some IBD medications (e.g., steroids, aminosalicylates, and anti-TNF-α agents), as well as the use of probiotics/prebiotics have been reported to positively affect either the composition/metabolism of gut microbiota or the metabolic status of intestinal cells by altering the intestinal biota [ 214 ]. These drugs/strategies may thus represent valid therapeutic options.…”
Section: Discussion and Therapeutic Perspectivesmentioning
confidence: 99%
“…Finally, it should be mentioned that some IBD medications (e.g., steroids, aminosalicylates, and anti-TNF-α agents), as well as the use of probiotics/prebiotics have been reported to positively affect either the composition/metabolism of gut microbiota or the metabolic status of intestinal cells by altering the intestinal biota [ 214 ]. These drugs/strategies may thus represent valid therapeutic options.…”
Section: Discussion and Therapeutic Perspectivesmentioning
confidence: 99%
“…It was reported that the postbiotics improve mucosal maturation and function and, furthermore, trigger the host’s immune system and anti-inflammatory responses [ 169 , 170 ]. Postbiotics are important for maintaining intestinal homeostasis and epithelial barrier function, as well as for establishing stable communities within gut microbiota; thus, the use of these bioactive compounds in IBD therapy is recommended [ 171 ].…”
Section: Postbiotics and Ucmentioning
confidence: 99%
“…In normal conditions, four phyla of microbiota are detected to be dominant in the gut of normal human, including Bacteroidetes , Firmicutes , Actinobacteria and Proteobacteria ( Zhang et al, 2017b ; Invernizzi et al, 2021 ; Mao et al, 2021 ). However, dysbiosis of intestinal microbiota has been investigated in patients with various digestive disorders, such as colorectal cancer and IBD ( Shin et al, 2015 ; Tomasello et al, 2016 ; Sun and Shen, 2018 ; Fan et al, 2021 ; Sultan et al, 2021 ). Under certain pathologic conditions, some kinds of harmful microbiota are invaded and largely residue in the gut.…”
Section: Autophagy In Inflammatory Bowel Diseasementioning
confidence: 99%